Bank's Liability Regarding The Implementation of Secrecy Principle For The Interest of The Corruption Court - Namira, Syifa; Sumerthayasa, Putu Gede Arya (Kertha Wicara : Journal Ilmu Hukum; Vol 9 No 9 (2020), 2020)
Bank’s secrecy principle requires bank to keep its customer’s data safe, in which the customer’s trusted the bank to save their deposits in. However, secrecy principle isn’t formally absolute. In other words, there are exceptions of the implementation of the principle itself, including corruption case. Therefore, there needs to be bank’s liability as a form of protection for the bank’s customers in order for the secrecy principle to be implemented well. This research’s purposes are to know the regulation regarding bank’s secrecy principle in a corruption case and the bank’s liability regarding bank’s secrecy principle for the matter of the court in a corruption case. Through normative method, this research is systematically arranged to be understood more easily. The results of this research show that the regulation regarding bank’s secrecy principle in a corruption case is regulated outside of the law of banking and the bank’s liability regarding the implementation of bank’s secrecy for the matter of the court in a corruption case is just the same as any other exceptional circumstances inside the law of banking.